Factors influencing knowledge productivity among administrative and diplomatic officers (PTD) / Nur Izzati Yusof - Yusof, Nur Izzati (Institute of Graduate Studies, UiTM, 2018)
Knowledge productivity, the central theme of this thesis, brings on new challenges in managing the knowledge workers in the 21st century. This thesis was embarked with the purpose to understand the relationship between job design and knowledge productivity among the Administrative and Diplomatic Officers (PTD). The PTD has been regarded as a premier knowledge worker in the Malaysian government. They primarily acts as a think tank in assisting the government in formulating and maintaining the public policies. In accordance with the rapid transformations in the age of information, the PTD is required to have knowledge and competencies to face the increasing responsibilities and upcoming challenges. Thus, it is the responsibility of the Malaysian Federal Ministries in overseeing the productivity of their knowledge workers. However, as a consequence of the transition towards the knowledge economy, most organizations including the public sectors are dumbfounded on understanding the drivers of productivity. The traditional factors for workers' productivity such as rewards and incomes may have lost its significance. Organizations clearly do not understand on the concept of knowledge productivity and how to make the knowledge more productive for the benefits of their knowledge workers and organizational improvements. In addition, based on the literature studies, the researcher found that there is lack of studies with regards to knowledge productivity in the context of Malaysia's public sectors. This has created big gaps on how to harness the PTDs' knowledge to become more productive. Identifying the factors that influence the PTD's knowledge productivity could facilitate the public sectors in enhancing their civil servants competencies…